IMPLEMENTASI FUNGSI POAC DALAM ADMINISTRASI DOKUMEN DIVISI TATA USAHA PADA SMK PERSADA BAGIA INFORMATIKA - Mahardika, Sabrina Fitria; Dwita, Febrisi (JURNAL MAHASISWA BINA INSANI; Vol 8 No 2 (2023): Jurnal Mahasiswa Bina Insani (November 2023), 2023)
Archives have a very important role in maintaining the smooth running of organizational activities as a source of information and memory storage. However, inadequate appreciation of the value of archives can cause problems, making the retrieval of stored archives increasingly difficult. This condition emphasizes the need for professional staff and adequate facilities to support the archiving process, so that it will result in improvements in overall archive management. By implementing efficient archive management, archives can be found easily when needed and their authenticity is maintained. This research uses a qualitative descriptive method, which systematically describes the facts, objects and characteristics of the objects studied accurately. The data obtained in this research is regarding the Implementation of Archives Management to Increase Efficiency in the Administrative Administration of Persada Bagia Informatics Vocational School. The techniques used include observation, interviews and documentation. Data analysis is carried out through data collection, reduction, presentation and verification. The results of the research show that Persada Bagia Informatika Melinting Vocational School has succeeded in implementing the stages of its Archives Management well. The preparation of archives is carried out in two stages, namely the preparation of incoming letters and outgoing letters. Archives are used by grouping archives into active and inactive. Archive storage is carried out using a chronological storage system. Archive maintenance is carried out periodically, namely every day, weekly and quarterly. Archives are destroyed through a process of inspection, selection and burning.